Variasi Bahasa Mahasiswa Perantau di Fakultas Bahasa dan Seni, Universitas Negeri Padang - Silvia Giofani; Noviani Suhardesi; Syahrul Ramadhan; Elfia Sukma; Norliza Jamaluddin (Universitas Palangka Raya, 2025)
This study analyzes the language variations among migrant students at the Faculty of language and Arts, Universitas Negeri Padang. Language variation arisesbnot only from the diversity of speakers but also from sicial interaction activities. The use of first languages and local dialects influences their language use, resulting in diverse language forms incluiding inddonesian, regional languages, and colloquial vvarieties. This researchaims to describe the types of language variations and the factors causing these variations. Using a qualitative descriptive approach with observation, recording, and note-taking techniques, the study finds that language variation among migrant students is influenced by social and situational factors, including environmental and kinship contexts. The findings contribute to sociolinguistic understanding of lasnguage use in multiculturar campus environments.